Uncovered versus covered metallic stents for the management of unresectable malignant distal biliary obstruction: a randomized multicenter trial. (3rd October 2021) - Sakai, Yuji; Sugiyama, Harutoshi; Kawaguchi, Yoshiaki; Kawashima, Yohei; Hirata, Nobuto; Nakaji, So; Natsui, Masaaki; Shioji, Kazuhiko; Nakahara, Kazunari; Tsuyuguchi, Toshio; Kato, Naoya
Abstract: Objective: The treatment result of the uncovered metallic stent (uncovered MS) and covered metallic stent (covered MS) for unresectable malignant distal biliary obstruction is controversial. This time, we conducted this study to compare the efficacies and complication rates of uncovered MS and covered MS in unresectable malignant distal biliary obstructions at a prospective randomized multicenter trial. Materials and methods: From April 2014 to September 2018, patients with unresectable malignant distal biliary obstruction were randomly assigned to 2 groups: the uncovered MS group and the covered MS group. Results: 92 treatment results patients were discussed. 48 patients were assigned to the uncovered MS group and 44 cases were assigned to the covered MS group. Both groups showed a drainage effect. No significant difference was found in the drainage effect between the 2 groups. The number of stent occlusion was significantly greater ( p = .0467) in uncovered MS (43.8%) comparing with those in covered MS (22.7%). As the cause of stent occlusion, tumor ingrowth was significantly greater ( p < .001) in the uncovered MS group (35.4%) than in the covered MS group (2.3%). The median stent patency period was significantly longer ( p = .0112) in the covered MS group (455 days) than that of the uncovered MS group (301 days). A significant difference in the median survival period was not found between the 2 groups. Conclusions: Covered MS showed the possibility of extending the stent patency period by suppressing tumor ingrowth more than uncovered MS does. The UMIN Clinical Trial Registry number is UMIN000015093.